Respuesta :

Answer:

see explanation

Step-by-step explanation:

Using the trigonometric identities

• sin²x + cos²x = 1

• cot x = [tex]\frac{cosx}{sinx}[/tex], csc x = [tex]\frac{1}{sinx}[/tex]

Consider the left side

[tex]\frac{1+cosx}{1-cosx}[/tex] - [tex]\frac{1-cosx}{1+cosx}[/tex]

Expressing as a single fraction

= [tex]\frac{(1+cosx)^2-(1-cosx)^2}{(1-cosx)(1+cosx)}[/tex]

Expand and simplify numerator/ denominator

= [tex]\frac{1+2cosx+cos^2x-1+2cosx-cos^2x}{1-cos^2x}[/tex]

= [tex]\frac{4cosx}{sin^2x}[/tex]

= [tex]\frac{4cosx}{sinx}[/tex] × [tex]\frac{1}{sinx}[/tex]

= 4cotxcscx = right side ⇒ verified